Analisis Faktor Karakteristik Orangtua Terhadap Frekuensi Konsumsi Fast Food Pada Remaja Siswa Kelas XI SMAIT Ukhuwah Banjarmasin - St. Hateriah; Esti Yuandari (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Parents have a role in influencing teenagers to consume fast food. Mothers who don't have time to prepare food at home because they are busy cause teenagers to use fast food as an alternative food. The aim of this research is to analyze parental characteristics regarding the frequency of fast food consumption in adolescents. This type of quantitative research uses descriptive observational with a cross sectional design. The research objects were Class XI students at SMAIT Ukhuwah Banjarmasin with a population of 173 students. Sampling used a simple random sample (Simple Random Sampling) totaling 52 people.The results of the research show that there is no influence of parental characteristics on the frequency of fast food consumption in adolescents, namely father's education with a p value of 0.14, Mother's education with a p value of 0.80, father's occupation with a p value of 0.70, Mother's occupation p value 0.62 and parents' income p value 0.83. The types of fast food that are most often consumed are Kentucky chicken, instant noodles and nuget. The frequency of fast food consumption shows that the most students are in the category "Frequently (>3x per week) as many as 31 people (59.6%), while the "Rarely" category (≤3x per week) was 21 people (40.4%). Descriptively, fast food consumption occurs more often in higher education groups in the PT category. The occupation of self-employed parents in fast food consumption is more dominant in the "Frequent" category, because job flexibility allows time and income to access fast food more easily. The group with the highest income continues to show dominance in fast food consumption in the "Frequent" category. There is a need to increase awareness of teenagers and families about the importance of maintaining a healthy and balanced diet.